2016
DOI: 10.5958/0975-6906.2016.00065.1
|View full text |Cite
|
Sign up to set email alerts
|

Accomplishments and challenges of pigeonpea breeding research in India

Abstract: Pigeonpea [Cajanus cajan (L.) Millsp.] is a protein-rich pulse crop which can grow well under soil moisture limited environments. The crop can play a significant role in meeting the challenges of global food security under the looming threats of climate change, soil degradation and rising production costs. This would be possible through fasttrack breeding of new cultivars with high and stable performances. This paper reviews the achievements of pigeonpea breeding research and suggests the growth trajectory for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The present result supports the findings of Rathod et al (2014) were they had recorded lowest mean M. vitrata larva per plant (1.8/plant) and pod damage (18.59%) in BSMR 853. Further the present result is supporting the findings of Anatharaju and Muthiah (2008) and Saxena et al (2016) who had reported that ICPL 332 (13 larva/6 plants) and C0-6 (18.33 larva/6 plants) had lowest Maruca infestation and Helicoverpa armigera tolerance. The genotype ICPL332 WR has resistance to fusarium wilt also (Sharma 2016).…”
Section: Screening Of Pigeonpea Genotypessupporting
confidence: 92%
See 1 more Smart Citation
“…The present result supports the findings of Rathod et al (2014) were they had recorded lowest mean M. vitrata larva per plant (1.8/plant) and pod damage (18.59%) in BSMR 853. Further the present result is supporting the findings of Anatharaju and Muthiah (2008) and Saxena et al (2016) who had reported that ICPL 332 (13 larva/6 plants) and C0-6 (18.33 larva/6 plants) had lowest Maruca infestation and Helicoverpa armigera tolerance. The genotype ICPL332 WR has resistance to fusarium wilt also (Sharma 2016).…”
Section: Screening Of Pigeonpea Genotypessupporting
confidence: 92%
“…Therefore while screening for legume pod borer resistance in pigeonpea these factors has to be considered and accordingly a screening programme as to be formulated. There exists a lack of targeted resistance breeding programme against M. vitrata in India and abroad (Saxena et al, 2016). The persistence effort to critically evaluate the resistance in existing genotypes against this insect pest in pigeonpea is the pioneer step for a targeted resistance 1 Division of Crop Protection, ICAR-Indian Institute of Pulses Research, Kanpur-208 024, Uttar Pradesh, India.…”
Section: Introductionmentioning
confidence: 99%
“…In the second phase of pigeonpea breeding emphasis was given to enhance specific traits through hybridization and pedigree selection. These included traits like early maturity, seed size, pod size, plant type, disease resistance and yield (Saxena, Sultana, et al, 2016). By using pedigree breeding a total of 89 pigeonpea varieties were released since 1960.…”
Section: The Popular Breeding Methods Used In Pigeonpeamentioning
confidence: 99%
“…The pigeonpea breeding accomplishments achieved in the past half century have recently been reviewed by Saxena, Sultana, et al (2016), Saxena, Sharma, and Vales (2019). The major conclusions were (a) achieved significant success in the genetic enhancement of simply inherited traits, but the yield harvests per unit area remained more or less the same, (b) developed high yielding resistant cultivars for Fusarium wilt and sterility mosaic diseases; and this has not only reduced the yield losses but also provided stability in the production at farmers’ level, (c) significantly reduced the crop maturity period from about 300 days to less than 90 days; and it has helped in diversifying cropping systems involving pigeonpea, and (iv) established hybrid technology, the first in any food legume, with an on‐farm yield advantage of 30%–50% or more.…”
Section: Breeding Accomplishmentsmentioning
confidence: 99%
“…cajan is one of India's most popular pulse crops (Nene, 2006;Pal et al, 2011;Sarkar et al, 2018;Fuller et al, 2019;Jorrin et al, 2021). In many parts of India, it is an attractive element of subsistence and rainfed farming systems (Saxena et al, 2016;Singh et al, 2016). Since, it is a hardy crop, C. cajan can be cultivated successfully either under rainfed or limited input condition (Daniel and Ong, 1990;Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%